Correction of attention disorders of children with special educational needs - Nogerova Mariam (SHS Web of Conferences, 2023)
The article is devoted to the problem of correcting the properties of arbitrary attention of younger schoolchildren with mental retardation and their underachieving peers. The essence and scientific definition of "attention", "attentiveness" and "properties of attention" is revealed. Specially created for children with mental retardation, the corrective program for the development of the properties of arbitrary attention is adapted to be used to correct the properties of attention of underachieving children in the mixed group. A comparative study of the correction of the properties of voluntary attention of younger pupils with mental retardation and their peers with low school performance was carried out. It was determined that the effectiveness of correcting the attention span of these categories of learners depends on a successful combination of group, individual, and pair work. Correctional group work is more effective for children with mental retardation if it is carried out together with underachieving children.